2022
DOI: 10.1055/a-1939-6110
|View full text |Cite
|
Sign up to set email alerts
|

Bending Pyrenacenes to Fill Gaps in Singlet-Fission-Based Solar Cells

Abstract: Singlet fission is envisaged to enhance the efficiency of single-junction solar cells beyond the current theoretical limit. Even though sensitizers that undergo singlet fission efficiently are known, characteristics like low-energy triplet state or insufficient stability restrict their use in silicon-based solar cells. Pyrenacenes have the potential to overcome these limitations, but singlet-fission processes in these materials is outcompeted by excimer formation. In this work, bent pyrenacenes with a reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Increasing the structural curvature of the PBI cores results in a red shift of the longest-wavelength absorption peaks from 527 nm ( 3″ ) to 544 nm ( 5a ), together with decreased extinction coefficients. This trend contrasts with those of pyrenophane and teropyrenophane, in which increased structural curvature leads to blue-shifted absorption spectra. , These results firmly corroborate the recent argument that the symmetry of the local orbitals in the K-region (bonding or antibonding) governs the (de)­stabilization of the HOMO and LUMO . The shortest-wavelength emission peaks also exhibited a bathochromic shift from 535 nm ( 3″ ) to 555 nm ( 5a ) with increasing curvature.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Increasing the structural curvature of the PBI cores results in a red shift of the longest-wavelength absorption peaks from 527 nm ( 3″ ) to 544 nm ( 5a ), together with decreased extinction coefficients. This trend contrasts with those of pyrenophane and teropyrenophane, in which increased structural curvature leads to blue-shifted absorption spectra. , These results firmly corroborate the recent argument that the symmetry of the local orbitals in the K-region (bonding or antibonding) governs the (de)­stabilization of the HOMO and LUMO . The shortest-wavelength emission peaks also exhibited a bathochromic shift from 535 nm ( 3″ ) to 555 nm ( 5a ) with increasing curvature.…”
Section: Resultssupporting
confidence: 84%
“…Our PBIphanes 5a – 5c contain nonconjugative alkyl tethers to induce the curvature of the π-system. Hence, 5a – 5c should be more suitable candidates to explore the effects of the bending of inherently planar PBIs on the chemical and physical properties of the π-conjugated cores, which has been a recent topic of high interest for the design of advanced organic electronic and optoelectronic materials. Twisted PBI derivatives with alkyl tethers have been studied by Würthner and co-workers. , …”
Section: Introductionmentioning
confidence: 99%
“…[30,32] Our study illustrates that we can leverage the typically undesired π-radical reactivity as a method for making novel functional materials-not only by building extended aromatic cores but also via inducing strain to access curved systems. The PLY cascade complements the rather limited pool of methods toward chiral peropyrenes, [30,[32][33][34] while the contortion of the PP unit makes compound 2 a promising singlet-fission material, as highlighted recently for bent pyrenacene [35] and rylene diimide [36] families. Moreover, by controlling the amount of oxidant, we could showcase a reversible two-state thermal magnetic switch, which is relevant in the context of responsive materials [37] for spintronics.…”
Section: Methodsmentioning
confidence: 97%
“…Given that the space between the aryl groups is already very small in symmetrical chiral peropyrenes, installing electronically opposing aryl substituents in the bay region could make new dynamic chiral peropyrenes with smaller HOMO−LUMO gaps and enhanced chiroptical properties. 20 Herein, we report the synthesis of the first dissymmetrical, axially chiral peropyrene using C−H activation on a complex pyrene system. Two different electron-deficient diyne derivatives were prepared to investigate the difference in the photophysical properties and barrier to rotation of the aryl groups in the bay regions relative to a previously reported symmetrical chiral peropyrene.…”
mentioning
confidence: 99%
“…They also showed that the aryl groups were ∼2.9 Å apart and the molecules, themselves, had a face-to-face interplanar molecular packing distance of 9.0 Å. Given that the space between the aryl groups is already very small in symmetrical chiral peropyrenes, installing electronically opposing aryl substituents in the bay region could make new dynamic chiral peropyrenes with smaller HOMO–LUMO gaps and enhanced chiroptical properties …”
mentioning
confidence: 99%